„Their Eagerness in Preaching of the God's Word“. Religious Orders and Counter-Reformation (Theatrum historiae, 2008)
The process of counter-reformation in the Czech lands after the Bílá hora battle (1620) was made more difficult not only for the resistance of non-catholics, but also for the lack of priests in the ecclesiastic administration. It was caused by the religious situation in the times of the Hussite revolution and then during the process of reformation in 16th century. That is the reason why the counter-reformation was as long as to the end of the 17th century mainly organised by the members of different religious orders. The so called old orders – Benedictins, Premonstratensians, Cistercians, etc. were renovated; and there also existed a strong influence of the new orders. Amongst the most successful we can find Jesuits and Piarists – both orders profiled as educational orders. Education of the youth in catholic doctrine is believed to be one of the key instruments that helped the counterreformation to succeed. It was also very important that the members of religious orders worked in many parishes as vicars. Comparing the particular regions of the Czech lands, the process of counter-reformation and the influence of religious orders differed; the position of non-catholics was stronger in Silesia only.